Electrolyte, battery and electric equipment
By using polyether as an infiltration additive in the lithium-ion battery electrolyte, the problem of insufficient wetting of the electrode active material in the electrolyte is solved, and higher battery circulation performance and longer life are achieved.
Patent Information
- Application Number
- CN202411914503.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-21
AI Technical Summary
The increase in electrode coating weight and compaction density in energy storage lithium-ion batteries leads to insufficient wetting of the electrolyte on the electrode active material, affecting the cycling performance of the battery.
An electrolyte containing polyether as an infiltration additive is used, and the end group of the polyether is a di(trimethylsiloxy)methylsilyl group. By adjusting the mass fraction of the infiltration additive and the proportion of the film-forming additive, the infiltration performance of the electrolyte is optimized.
The wetting efficiency of the electrolyte on the positive electrode sheet and the negative electrode sheet is improved, the transmission impedance of lithium ions is reduced, the cycle life of the battery is extended, and the preparation efficiency is improved.
Smart Images

Figure CN119674222A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrolyte, a battery and an electrical device. Background Art
[0002] With the development of the energy storage industry, lithium-ion battery technology continues to develop. Whether it is the wind and solar power generation side, household energy storage side or other user scenarios, lithium-ion energy storage batteries have lower costs and higher energy density requirements. For energy storage lithium-ion batteries, one of the ways to reduce costs and increase battery energy density is to achieve higher electrode coating and higher cold pressing density. On the basis of the same active material capacity, the use of current collector layers and other materials is reduced to achieve the purpose of reducing costs. At the same time, due to the highly concentrated distribution of materials, the battery can achieve higher energy density at the same mass and volume.
[0003] However, as the electrode coating weight and compaction density in energy storage lithium-ion batteries increase, the problem of insufficient wettability of the electrolyte to the electrode active material becomes prominent, which may lead to lithium precipitation, thereby reducing the cycle performance of the battery. Therefore, it is an urgent problem to provide an electrolyte with good wettability to the electrode active material. Summary of the invention
[0004] In view of this, the present application provides an electrolyte, a battery and an electrical device, wherein the electrolyte has good wetting properties.
[0005] The present application provides an electrolyte, the electrolyte comprising a wetting additive, the wetting additive being a polyether, and the end group of the wetting additive comprising a di(trimethylsilyloxy)methylsilyl group.
[0006] Furthermore, the structural formula of the wetting additive is: The range of n is: 2≤n≤20.
[0007] Furthermore, in the electrolyte, the mass fraction a of the wetting additive is in the range of 0.05%≤a≤2%.
[0008] Furthermore, the electrolyte further includes a film-forming additive, and the film-forming additive is a cyclic carbonate additive. In the electrolyte, the mass fraction of the film-forming additive is b, and the electrolyte satisfies the relationship: 0.02≤a / b≤4.
[0009] Furthermore, the mass fraction b of the film-forming additive is in the range of 0.2%≤b≤8%.
[0010] Further, the film-forming additive includes at least one of vinylene carbonate, 4,5-dimethylvinylene carbonate, 4,5-divinylvinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, catechol carbonate, vinylethylene carbonate, trifluoropropylene carbonate, and methyleneethylene carbonate.
[0011] Furthermore, the wetting additive is selected from and One or more of .
[0012] Furthermore, the electrolyte further comprises a solvent, and the solvent is used to dissolve the wetting additive. In the electrolyte, the mass fraction c of the solvent is in the range of 50%≤c≤90%.
[0013] The present application also provides a battery, which includes: a positive electrode plate, a separator, a negative electrode plate and an electrolyte provided by the present application; the electrolyte is used to infiltrate at least a portion of the positive electrode plate, the separator and the negative electrode plate.
[0014] The present application also provides an electrical device, which includes: a device body and a battery provided in the present application, and the battery supplies power to the device body.
[0015] In the present application, the electrolyte is applied to a battery, and the electrolyte includes a wetting additive to enhance the wetting performance of the electrolyte on the positive electrode plate, the diaphragm and the negative electrode plate. When the energy density of the battery is large, that is, more positive electrode active materials are coated in the positive electrode plate and more negative electrode active materials are coated in the negative electrode plate, the electrolyte can still uniformly wet the positive electrode plate and the negative electrode plate to reduce the impedance of lithium ion transmission in the battery, thereby enabling the battery to have better cycle performance and longer cycle life.
[0016] Specifically, the wetting additive is a polyether, and the terminal group of the wetting additive is a di(trimethylsiloxy)methylsilyl group. In the wetting additive, the polyether can be used as a hydrophilic functional group, and the di(trimethylsiloxy)methylsilyl group can be used as a hydrophobic functional group. In other words, the wetting additive contains both a hydrophilic polyether and a hydrophobic di(trimethylsiloxy)methylsilyl group, and the polyether and the di(trimethylsiloxy)methylsilyl group are arranged relative to each other. When the wetting additive is applied to an electrolyte, the functional groups with different wettability have different affinities for the electrolyte. The hydrophilic ether oxygen segment faces the inside of the electrolyte, and the hydrophobic di(trimethylsiloxy)methylsilyl group faces the air, so that the wetting additive is enriched at the interface between the electrolyte and the air. Compared with the solution that does not include wetting additives in the electrolyte, the wetting additives of the present application can serve as a transition substance between the electrolyte and the air, so that one side of the wetting additive has better compatibility with the electrolyte, and the other side is repelled from the interface between the electrolyte and the air, which is beneficial to reduce the attraction of the electrolyte to the interfacial molecular layer on the side of the electrolyte close to the air, thereby reducing the surface tension of the electrolyte. When the electrolyte is applied to a battery, the hydrophobic di(trimethylsilyloxy)methylsilyl group is closer to the positive electrode active material and the negative electrode active material than the polyether, thereby reducing the specific surface energy difference between the electrolyte and the positive electrode active material, and reducing the specific surface energy difference between the electrolyte and the negative electrode active material, thereby reducing the wetting angle between the electrolyte and the positive electrode active material, and reducing the wetting angle between the electrolyte and the negative electrode active material. On the one hand, it is beneficial to improve the wetting efficiency of the electrolyte on the positive electrode sheet and the negative electrode sheet, and reduce the wetting time of the electrolyte on the positive electrode sheet and the negative electrode sheet, thereby shortening the preparation cycle of the battery and improving the preparation efficiency of the battery. On the other hand, the electrolyte can improve the wetting performance of the positive electrode active material and the negative electrode active material, improve the wetting effect of the electrolyte on the positive electrode sheet and the negative electrode sheet, so as to improve the uniformity of the electrolyte infiltrating the positive electrode sheet and the negative electrode sheet, avoid the lithium precipitation phenomenon due to insufficient wetting, improve the cycle performance of the battery when the electrolyte is applied to the battery, and extend the cycle life of the battery. On the other hand, the polyether and the di(trimethylsiloxy)methylsilyl group have good stability in the electrolyte. When the electrolyte is applied to the battery and the battery is in the process of charging and discharging, the polyether and the di(trimethylsiloxy)methylsilyl group can be prevented from being decomposed within the normal operating voltage range of the battery, and the side reaction of the wetting additive can be avoided, and it is ensured that the wetting additive can fully play the role of improving the wetting performance of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 A partial cross-sectional structural schematic diagram of a battery according to an embodiment of the present application;
[0019] Figure 2 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application;
[0020] Figure 3 This is a circuit block diagram of an electrical device according to an embodiment of the present application.
[0021] Description of reference numerals:
[0022] 100-electrolyte, 200-battery, 210-positive electrode plate, 220-diaphragm, 230-negative electrode plate, 300-electrical equipment, 310-equipment body. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0024] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0025] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0026] With the development of the energy storage industry, lithium-ion battery technology continues to develop. Whether it is the wind and solar power generation side, household energy storage side or other user scenarios, lithium-ion energy storage batteries have lower costs and higher energy density requirements. For energy storage lithium-ion batteries, one of the ways to reduce costs and increase battery energy density is to achieve higher electrode coating and higher cold pressing density. On the basis of the same active material capacity, the use of current collector layers and other materials is reduced to achieve the purpose of reducing costs. At the same time, due to the highly concentrated distribution of materials, the battery can achieve higher energy density at the same mass and volume.
[0027] At present, the electrolyte in liquid lithium-ion batteries uses a mixed solvent of cyclic carbonate and chain carbonate; on the one hand, the viscosity of such aprotic solvents is relatively high and the surface tension is relatively large; when injecting liquid, the pourability of such mixed solvents is not very good, making it difficult for the electrolyte to infiltrate the electrode active materials. On the other hand, the affinity of polyethylene and polypropylene diaphragm materials with electrolytes is small, resulting in poor wettability of electrolytes to diaphragms; on the other hand, with the increase of electrode coating weight and compaction density in energy storage lithium-ion batteries, the space between the electrode assembly and the shell is very small, making it very difficult to inject electrolytes. The wettability of aprotic solvents to positive and negative active materials with high specific surface areas is not very good, which will cause the contact resistance between the electrode material and the electrolyte to be relatively large, making it difficult to meet the requirements of low internal resistance of lithium-ion batteries; the poor wettability of electrolytes to electrode active materials will affect the utilization rate of positive and negative electrode materials, which is not conducive to the use of battery capacity.
[0028] From the above, it can be seen that while improving the coating quality and compaction density of the electrode, the problem of insufficient wettability of the electrolyte to the electrode active material has become prominent, which is specifically manifested in: First, during the injection of the electrolyte, as the compaction density of the electrode increases, the infiltration time of the electrolyte to the electrode sheet increases, resulting in a longer battery cell preparation cycle; Second, compared with the infiltration of the electrolyte to the electrode sheet with low coating quality, the degree of electrolyte infiltration in the electrode sheet with high coating quality deteriorates significantly. This is because as the coating quality of the electrode active material increases, the gap inside the active material decreases, and the path for the electrolyte to infiltrate the active material becomes longer and more tortuous, resulting in inconsistent infiltration of the electrolyte on the electrode sheet. During the charge and discharge process, the active materials in the electrode consume the electrolyte, which reduces the electrolyte content of the active materials in the active material layer close to the current collector, resulting in the inability of lithium ions to be smoothly transmitted and infiltrate the active materials in the active material layer far from the current collector. As a result, there is a shortage of lithium ions inside the active material layer and an excess of lithium ions on the surface of the active material layer, which leads to lithium deposition and deterioration of battery performance. Therefore, it is an urgent problem to provide an electrolyte with good wetting properties for electrode active materials.
[0029] Furthermore, as the coating mass of the active material of the battery increases, the internal voids of the battery further decrease. When the battery shell is consistent, the content of the electrolyte injected into the battery decreases, and the electrode assembly with high coating mass consumes the electrolyte at a faster rate, shortening the cycle life of the battery. Therefore, it is necessary to further reduce the consumption of the electrolyte and extend the service life of the battery by slowing down the consumption of the electrolyte.
[0030] In the terminology of this application, "electrode coating" refers to the active material coated in the electrode assembly, and "electrode assembly" refers to the structure formed by the positive electrode sheet, the separator and the negative electrode sheet.
[0031] See also Figure 1 The present application provides a battery 200, which includes a positive electrode plate 210, a separator 220, a negative electrode plate 230 and an electrolyte 100 provided in the present application; the electrolyte 100 is used to infiltrate at least a portion of the positive electrode plate 210, the separator 220 and the negative electrode plate 230.
[0032] It can be understood that the separator 220 is disposed on one side of the positive electrode plate 210 ; and the negative electrode plate 230 is disposed on the side of the separator 220 away from the positive electrode plate 210 .
[0033] It can be understood that the positive electrode sheet 210 , the separator 220 , and the negative electrode sheet 230 are stacked, and the positive electrode sheet 210 , the separator 220 , and the negative electrode sheet 230 form an electrode assembly.
[0034] Optionally, in some embodiments, the battery 200 is a lithium-ion battery.
[0035] It can be understood that the electrolyte 100 is used to infiltrate the positive electrode sheet 210, the separator 220 and the negative electrode sheet 230 to achieve the transmission of active ions in the battery 200 between the positive electrode sheet 210 and the negative electrode sheet 230. When the battery 200 is a lithium-ion battery, the active ions are lithium ions.
[0036] It can be understood that the positive electrode plate 210 includes a positive electrode active material, and the negative electrode plate 230 includes a negative electrode active material. During the charging process of the battery 200, lithium ions are released from the positive electrode active material of the positive electrode plate 210 and embedded in the negative electrode active material of the negative electrode plate 230 through the electrolyte 100; during the discharging process of the battery 200, lithium ions are released from the negative electrode active material of the negative electrode plate 230 and embedded in the negative electrode active material of the positive electrode plate 210 through the electrolyte 100.
[0037] In the present embodiment, the battery 200 includes the electrolyte 100 provided in the embodiment of the present application, and the electrolyte 100 includes a wetting additive, and the wetting additive contains both a hydrophilic polyether and a hydrophobic di(trimethylsiloxy)methylsilyl group, and the polyether and the di(trimethylsiloxy)methylsilyl group are arranged relative to each other. When the wetting additive is applied to the electrolyte 100, the functional groups with different wettability have different affinities for the electrolyte 100, the hydrophilic ether oxygen segments are oriented toward the inside of the electrolyte 100, and the hydrophobic di(trimethylsiloxy)methylsilyl groups are arranged toward the air, so that the wetting additive is enriched at the interface between the electrolyte 100 and the air, and the wetting additive can serve as a transitional substance between the electrolyte 100 and the air, so that one side of the wetting additive has better compatibility with the electrolyte 100, and the other side is repelled at the interface between the electrolyte 100 and the air, which is beneficial to reduce The attraction of the inner part of the low electrolyte 100 to the interface molecular layer on the side of the electrolyte 100 close to the air is reduced, so as to reduce the surface tension of the electrolyte 100, so that the electrolyte 100 has a good wetting effect on the positive electrode sheet 210 and the negative electrode sheet 230, which is specifically manifested in that the positive electrode sheet 210 and the negative electrode sheet 230 can be fully and evenly infiltrated. In addition, the electrolyte 100 has a high wetting effect on the positive electrode sheet 210 and the negative electrode sheet 230, which is conducive to shortening the preparation cycle of the battery 200 and improving the preparation efficiency of the battery 200. The battery 200 of this embodiment not only has good cycle performance and a long cycle life, but also has a high preparation efficiency.
[0038] Optionally, in some embodiments, the diaphragm 220 is a polypropylene diaphragm 220 , a polyethylene diaphragm 220 , or a coated diaphragm 220 .
[0039] Optionally, the positive electrode sheet 210 includes a positive electrode current collector layer and a positive electrode material layer stacked, the positive electrode material layer is arranged on the surface of the positive electrode current collector layer, and the positive electrode material layer includes the positive electrode active material. The negative electrode sheet 230 includes a negative electrode current collector layer and a negative electrode material layer stacked, the negative electrode material layer is arranged on the surface of the negative electrode current collector layer, and the negative electrode material layer includes the negative electrode active material.
[0040] Optionally, in some embodiments, the positive electrode active material is LiFePO4, and the negative electrode active material is graphite.
[0041] It can be understood that when the coating mass of the positive electrode active material in the positive electrode material layer increases and the coating mass of the negative electrode active material in the negative electrode material layer increases, the coating mass of the electrode assembly increases and the energy density of the battery 200 increases.
[0042] The present application provides an electrolyte 100 , wherein the electrolyte 100 includes a wetting additive, wherein the wetting additive is a polyether, and wherein the end group of the wetting additive includes a di(trimethylsilyloxy)methylsilyl group.
[0043] It can be understood that the polyether is a chain structure containing oxygen atoms and carbon atoms, and the polyether is composed of a plurality of repeating units -OCO- (ether bonds).
[0044] In this embodiment, the electrolyte 100 is applied to the battery 200, and the electrolyte 100 includes a wetting additive to enhance the wetting performance of the electrolyte 100 on the positive electrode plate 210, the diaphragm 220 and the negative electrode plate 230. When the energy density of the battery 200 is relatively large, that is, more positive electrode active materials are coated in the positive electrode plate 210 and more negative electrode active materials are coated in the negative electrode plate 230, the electrolyte 100 can still uniformly wet the positive electrode plate 210 and the negative electrode plate 230 to reduce the impedance of lithium ion transmission in the battery 200, thereby enabling the battery 200 to have better cycle performance and longer cycle life.
[0045] Specifically, the wetting additive is a polyether, and the terminal group of the wetting additive is a di(trimethylsiloxy)methylsilyl group. In the wetting additive, the polyether can be used as a hydrophilic functional group, and the di(trimethylsiloxy)methylsilyl group can be used as a hydrophobic functional group. In other words, the wetting additive contains both a hydrophilic polyether and a hydrophobic di(trimethylsiloxy)methylsilyl group, and the polyether and the di(trimethylsiloxy)methylsilyl group are arranged relative to each other. When the wetting additive is applied to the electrolyte 100, the functional groups with different wettability have different affinities for the electrolyte 100. The hydrophilic ether oxygen segment faces the inside of the electrolyte 100, and the hydrophobic di(trimethylsiloxy)methylsilyl group faces the air, so that the wetting additive is enriched at the interface between the electrolyte 100 and the air. Compared with the solution in which the electrolyte 100 does not include a wetting additive, the wetting additive of the present application can serve as a transition substance between the electrolyte 100 and the air, so that one side of the wetting additive has better compatibility with the electrolyte 100, and the other side is repelled from the interface between the electrolyte 100 and the air, which is beneficial to reduce the attraction of the electrolyte 100 to the interface molecular layer on the side of the electrolyte 100 close to the air, thereby reducing the surface tension of the electrolyte 100. When the electrolyte 100 is applied to the battery 200, the hydrophobic di(trimethylsiloxy)methylsilyl group is closer to the positive electrode active material and the negative electrode active material than the polyether, thereby reducing the specific surface energy difference between the electrolyte 100 and the positive electrode active material, and reducing the specific surface energy difference between the electrolyte 100 and the negative electrode active material, thereby reducing the wetting angle between the electrolyte 100 and the positive electrode active material, and reducing the wetting angle between the electrolyte 100 and the negative electrode active material. On the one hand, it is beneficial to improve the wetting efficiency of the electrolyte 100 on the positive electrode sheet 210 and the negative electrode sheet 230, and reduce the wetting time of the electrolyte 100 on the positive electrode sheet 210 and the negative electrode sheet 230, thereby shortening the preparation cycle of the battery 200 and improving the preparation efficiency of the battery 200. On the other hand, the wetting performance of the electrolyte 100 on the positive electrode active material and the negative electrode active material can be improved, and the wetting effect of the electrolyte 100 on the positive electrode plate 210 and the negative electrode plate 230 can be improved, so as to improve the uniformity of the electrolyte 100 wetting the positive electrode plate 210 and the negative electrode plate 230, avoid lithium precipitation due to insufficient wetting, improve the cycle performance of the battery 200 when the electrolyte 100 is applied to the battery 200, and extend the cycle life of the battery 200.On the other hand, the polyether and the di(trimethylsiloxy)methylsilyl group have good stability in the electrolyte 100. When the electrolyte 100 is applied to the battery 200 and the battery 200 is in the process of charging and discharging, the polyether and the di(trimethylsiloxy)methylsilyl group can be prevented from being decomposed within the normal operating voltage range of the battery 200, the side reactions of the wetting additive can be avoided, and the wetting additive can be ensured to fully play the role of improving the wetting performance of the electrolyte 100.
[0046] It can be understood that in the terms of the present application, "hydrophilicity" and "hydrophobicity" are relative terms. "Hydrophilicity" refers to the property of a substance that can be wetted, absorbed or dissolved in water, and the affinity between the substance and water is relatively large. "Hydrophobicity" refers to the property that a substance and water repel each other, and it is not easily wetted by water or dissolved in water, and the affinity between the substance and water is relatively small.
[0047] It can be understood that in the terminology of this application, "wetting angle" refers to the angle between the solid-liquid interface through the liquid interior to the gas-liquid interface at the interface of solid, liquid and gas, also known as "contact angle". The smaller the wetting angle between the electrolyte 100 and the positive electrode active material and / or the negative electrode active material, the better the wetting effect of the electrolyte 100 on the positive electrode active material and / or the negative electrode active material. Correspondingly, the larger the wetting angle between the electrolyte 100 and the positive electrode active material and / or the negative electrode active material, the worse the wetting effect of the electrolyte 100 on the positive electrode active material and / or the negative electrode active material.
[0048] It can be understood that in the terminology of the present application, "specific surface energy difference" refers to the difference between the specific surface layers of different material surfaces. The greater the specific surface energy difference between the electrolyte 100 and the positive electrode active material and / or the negative electrode active material, the more difficult it is for the electrolyte 100 to infiltrate the positive electrode active material and / or the negative electrode active material; the smaller the specific surface energy difference between the electrolyte 100 and the positive electrode active material and / or the negative electrode active material, the easier it is for the electrolyte 100 to infiltrate the positive electrode active material and / or the negative electrode active material.
[0049] It can be understood that in the terminal bis(trimethylsilyloxy)methylsilyl, three silicon atoms and two oxygen atoms are included, and silicon and oxygen appear alternately in a chain arrangement, and the second silicon atom is located at the end of the polyether. The terminal group of the present application is a chain structure, and its steric hindrance is small, so that it has good hydrophobicity. If the silicon atoms and oxygen atoms are alternately arranged and arranged in a ring, the surface tension of the ring structure is large, making it poor in hydrophobicity. In addition, the second silicon atom of the end group is located at the end of the polyether, which is conducive to the end group being firmly set on the polyether, and when the wetting additive is applied to the electrolyte 100, functional groups with different wettability can be formed on both sides of the wetting additive, that is, one side of the wetting additive is a hydrophobic di(trimethylsiloxy)methylsilyl group, and one side of the wetting additive is a hydrophilic polyether structure, so that the wetting additive can be enriched in the surface molecular layer of the electrolyte 100 close to the air, so as to serve as a transition substance between the electrolyte 100 and the air, so as to facilitate the wetting of the positive electrode plate 210 and the negative electrode plate 230 by the wetting additive.
[0050] Optionally, in some embodiments, the structural formula of the wetting additive is: The range of n is: 2≤n≤20.
[0051] Specifically, the value of n can be, but is not limited to, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 and 20, etc.
[0052] It can be understood that in the sizing additive, the repeating unit of the polyether is -OCO- (ether bond), and the degree of polymerization of the repeating unit is n.
[0053] In this embodiment, the structural formula of the infiltration additive is: The impregnating additive has a polyether main chain and a di(trimethylsiloxy)methylsilyl group as an end group, so the side of the impregnating additive away from the di(trimethylsiloxy)methylsilyl group is hydrophilic, and the side of the impregnating additive with the di(trimethylsiloxy)methylsilyl group is hydrophobic. In other words, the opposite ends of the impregnating additive have different wettabilities, so that the impregnating additive can be used as a transitional substance between the electrolyte 100 and the air, and the hydrophilic ether oxygen segment faces the inside of the electrolyte 100, so that the impregnating additive has a better effect on the electrolyte 100. The compatibility of the electrolyte 100 and the negative electrode sheet 210 is improved by the addition of the hydrophobic bis(trimethylsiloxy)methylsilyl group toward the air, so that one side of the wetting additive is repelled from the interface between the electrolyte 100 and the air, thereby reducing the attraction of the electrolyte 100 to the interface molecular layer on the side of the electrolyte 100 close to the air, thereby reducing the surface tension of the electrolyte 100, and then making the electrolyte 100 have better wetting performance and wetting effect on the positive electrode sheet 210 and the negative electrode sheet 230, which is beneficial to improving the wetting efficiency of the electrolyte 100 on the positive electrode sheet 210 and the negative electrode sheet 230.
[0054] In the wetting additive provided in this embodiment, the repeating unit ether oxygen structure of the polyether chelates lithium ions. When the value of n satisfies the range of 2≤n≤20, in the polyether, the number of repeating units is within a reasonable range, so that the mass fraction of the wetting additive is within a reasonable range. On the one hand, the wetting additive can be uniformly enriched in the contact interface between the electrolyte 100 and the positive electrode sheet 210 and the negative electrode sheet 230 to reduce the specific surface energy difference between the electrolyte 100 and the negative electrode sheet 230 and the positive electrode sheet 210, so that the electrolyte 100 has better wetting performance on the positive electrode sheet 210 and the negative electrode sheet 230. On the other hand, when the value of n is within a reasonable range, the impregnation additive will chelate part of the lithium ions, which can prevent the electrolyte 100 from chelating too many lithium ions and causing excessive binding of lithium ions, so that the active ions in the electrolyte 100 can participate in the electrochemical reaction, so that the battery 200 has a higher capacity and better cycle performance when the electrolyte 100 is applied to the battery 200. When the value of n is too large, the number of repeating units is too large, and accordingly, the chain segment of the polyether is too long, and there are more ether oxygen structures in the impregnation additive, so that when the impregnation additive is applied to the electrolyte 100, more ether oxygen structures will chelate more lithium ions, so that the impregnation additive binds too many lithium ions, thereby reducing the amount of active ions in the electrolyte 100, and reducing the capacity and energy efficiency of the battery 200 when the electrolyte 100 is applied to the battery 200.
[0055] It can be understood that, in the terminology of the present application, "ether oxygen structure" specifically refers to the repeating unit -OCO- in the polyether.
[0056] Preferably, the range of n is: 5≤n≤15. Specifically, the value of n can be, but is not limited to, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 and 15.
[0057] More preferably, the value of n is 8.
[0058] Specifically, in some embodiments, the wetting additive is selected from and The wetting additive has good wetting performance on the positive electrode sheet 210 and the negative electrode sheet 230, and can prevent the ether bond from chelating too many lithium ions and reducing the amount of active lithium ions in the electrolyte 100, so that the battery 200 has good cycle performance and high energy efficiency.
[0059] Optionally, in some embodiments, in the electrolyte 100, the mass fraction a of the wetting additive is in the range of 0.05%≤a≤2%.
[0060] It can be understood that, in the electrolyte 100 , the mass fraction a of the wetting additive is the ratio of the mass of the wetting additive to the mass of the electrolyte 100 .
[0061] Specifically, the mass fraction a of the wetting additive may be, but is not limited to, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.7%, 0.8%, 1%, 1.1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.7%, 1.9% and 2%, etc.
[0062] In the electrolyte 100 provided in this embodiment, when the value of the mass fraction a of the wetting additive satisfies the range of 0.05%≤a≤2%, the mass fraction of the wetting additive is within a reasonable range. On the one hand, the wetting additive can give full play to its performance to be enriched in the surface molecular layer of the electrolyte 100 close to the positive electrode sheet 210 and the negative electrode sheet 230, so as to reduce the specific surface energy difference between the electrolyte 100 and the positive electrode sheet 210, and reduce the specific surface energy difference between the electrolyte 100 and the negative electrode sheet 230, so that the electrolyte 100 has better wetting performance on the positive electrode sheet 210 and the negative electrode sheet 230. Even if the coating weight of the positive electrode active material in the positive electrode sheet 210 is large, and / or the coating weight of the negative electrode active material in the negative electrode sheet 230 is large, the electrolyte 100 can still fully infiltrate the positive electrode active material and / or the negative electrode active material, so that the internal resistance of the battery 200 is small, and the battery 200 has good cycle performance. On the other hand, the impregnating additive has an ether bond, and the ether bond can chelate the lithium ions in the electrolyte 100, so that the impregnating additive preferentially adheres to the interface of the negative electrode sheet 230, which is convenient for further forming a stable SEI (Solid Electrolyte Interface) film on the interface between the negative electrode sheet 230 and the electrolyte 100, thereby further improving the cycle performance of the battery 200. In addition, it can be avoided that the impregnating additive binds too many lithium ions and reduces the capacity and energy efficiency of the battery 200. When the mass fraction of the wetting additive is too large, the wetting additive has a higher priority in coordination and chelation with the lithium ions than other components in the electrolyte 100. Accordingly, the more ether bonds in the wetting additive, the more lithium ions chelated and bound by the wetting additive, which reduces the rate of migration of the lithium ions in the electrolyte 100, thereby increasing the polarization of the battery 200, increasing the internal resistance of the battery 200, reducing the rate performance and energy efficiency of the battery 200, and also reducing the cycle stability of the battery 200. When the mass fraction of the wetting additive is too small, the wetting additive has no obvious effect on improving the wetting performance of the electrolyte 100, making it difficult for the electrolyte 100 to fully wet the positive electrode plate 210 and the negative electrode plate 230, thereby reducing the performance of the electrolyte 100 and shortening the cycle life of the battery 200 when the electrolyte 100 is applied to the battery 200.
[0063] In the terminology of the present application, "polarization" refers to the phenomenon that the electrodes (positive electrode sheet 210 and / or negative electrode sheet 230) deviate from their equilibrium potential during the charge and discharge process of the battery 200.
[0064] Preferably, in the electrolyte 100, the mass fraction a of the wetting additive is in the range of 0.05%≤a≤0.5%. Specifically, the mass fraction a of the wetting additive may be, but is not limited to, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc.
[0065] Optionally, in some embodiments, the electrolyte 100 further includes a film-forming additive, and the film-forming additive is a cyclic carbonate additive.
[0066] In this embodiment, the electrolyte 100 includes the wetting additive and the film-forming additive, and the film-forming additive is a cyclic carbonate additive. When the electrolyte 100 is applied to the battery 200, even if the coating weight of the positive electrode active material of the positive electrode plate 210 and the coating weight of the negative electrode active material of the negative electrode plate 230 are large and the energy density of the battery 200 is high, the wetting additive can fully wet the positive electrode active material and the negative electrode active material, so that the electrolyte 100 can be evenly distributed around the negative electrode active material. Accordingly, the film-forming additive can be evenly distributed around the negative electrode active material, so that a more uniform film can be formed on the surface of the negative electrode active material. In addition, the wetting additive and the film-forming additive cooperate with each other, the wetting additive can chelate free lithium ions in the electrolyte 100, and the wetting additive is preferentially adsorbed on the surface of the negative electrode plate 230 when the battery 200 is formed. When the film-forming additive is decomposed, the film-forming additive is more likely to generate a SEI film with a higher degree of polymerization under the influence of the electron-donating effect of the ether bond of the wetting additive, and is uniformly attached to the surface of the negative electrode plate 230 with the wetting additive as a fulcrum. The SEI film formed on the surface of the negative electrode plate 230 by the wetting additive and the film-forming additive not only has a high degree of polymerization, but also has high stability, which can slow down the speed at which the electrolyte 100 is consumed in the charge and discharge cycle. In other words, the electrolyte 100 has a good low consumption capacity, so that the battery 200 has a good cycle performance. Furthermore, the film-forming additive has a ring structure. Compared with the solution in which the film-forming additive has a chain structure, the film-forming additive of the present application is easier to open the ring under the electron donation effect of the ether bond, and is easier to form a SEI film with a higher degree of polymerization, so as to adhere to the surface of the negative electrode plate 230, so that the interface between the negative electrode plate 230 and the electrolyte 100 has a stable SEI film with a high degree of polymerization. It is known that the higher the degree of polymerization of the SEI film, the lower its solubility in the electrolyte 100, and the less soluble it is in the electrolyte 100, so that the SEI film has a higher stability in the electrolyte 100, so as to further slow down the consumption of the electrolyte 100 in the subsequent charging and discharging process, further improve the low consumption capacity of the electrolyte 100, and further extend the service life of the battery 200.
[0067] It can be understood that, in the terminology of the present application, “formation” refers to the process of charging the battery 200 after injection with a small current to activate the active materials inside the battery 200 .
[0068] It is understandable that in the terminology of the present application, "low consumption capability of the electrolyte 100" refers to the amount of energy consumed per unit time by the electrolyte 100. It is understandable that the more stable the SEI film is, the less amount of the electrolyte 100 is used to repair the SEI film, and the electrolyte 100 has better low consumption capability.
[0069] Optionally, in some embodiments, in the electrolyte 100, the mass fraction of the film-forming additive is b, and the electrolyte 100 satisfies the relationship: 0.02≤a / b≤4.
[0070] It can be understood that in the electrolyte 100 , the mass fraction b of the film-forming additive is the ratio of the mass of the film-forming additive to the mass fraction of the electrolyte 100 .
[0071] Specifically, the value of a / b can be, but is not limited to, 0.02, 0.05, 0.1, 0.15, 0.2, 0.4, 0.6, 0.8, 1, 1.5, 1.8, 2, 2.2, 2.4, 2.6, 3, 3.2, 3.5, 3.6, 3.8 and 4, etc.
[0072] In this embodiment, when the electrolyte 100 satisfies the relationship 0.02≤a / b≤4, the mass fraction a of the wetting additive and the mass fraction b of the film-forming additive are both within a reasonable range, and the wetting additive and the film-forming additive have a good synergistic effect. On the one hand, the wetting additive can be enriched in the contact interface between the electrolyte 100 and the positive electrode sheet 210 and the negative electrode sheet 230. The wetting additive serves as a transition substance between the electrolyte 100 and the positive electrode sheet 210 and the negative electrode sheet 230 to enhance the wetting performance of the electrolyte 100 on the positive electrode sheet 210 and the negative electrode sheet 230, thereby enhancing the cycle performance of the battery 200. On the other hand, the wetting additive cooperates with the film-forming additive so that the film-forming additive is evenly dispersed on the surface of the negative electrode plate 230, and forms a uniform, stable and highly polymerized SEI film on the surface of the negative electrode plate 230 to slow down the consumption rate of the electrolyte 100 during the charge and discharge cycle of the battery 200. In summary, the wetting additive improves the wetting performance of the electrolyte 100, and the wetting additive and the film-forming additive cooperate with each other to improve the low consumption performance of the electrolyte 100, thereby improving the cycle performance of the battery 200 when the electrolyte 100 is applied to the battery 200. When the value of a / b is too large, the mass fraction a of the wetting additive is too large, or the mass fraction b of the film-forming additive is too small. If the mass fraction of the wetting additive is too large, accordingly, there are too many ether bonds in the wetting additive, so that the wetting additive chelates and binds too many lithium ions, reducing the migration rate of the lithium ions in the electrolyte 100, thereby increasing the polarization of the battery 200, so that the internal resistance of the battery 200 increases, reducing the rate performance and energy efficiency of the battery 200, and also reducing the cycle stability of the battery 200. When the mass fraction of the film-forming additive is too small, the SEI film formed by the film-forming additive on the surface of the negative electrode plate 230 is too thin, and the SEI film is easy to rupture and form some highly active sites, which accelerates the deposition and dissolution rate of lithium ions at these sites, so that lithium precipitation and other phenomena may occur, reducing the safety performance of the battery 200. When the value of a / b is too small, the mass fraction a of the wetting additive is too small, or the mass fraction b of the film-forming additive is too large. When the mass fraction of the wetting additive is too small, the wetting additive has no obvious effect on improving the wetting performance of the electrolyte 100, making it difficult for the electrolyte 100 to fully wet the positive electrode sheet 210 and the negative electrode sheet 230, thereby reducing the performance of the electrolyte 100 and shortening the cycle life of the battery 200 when the electrolyte 100 is applied to the battery 200.In addition, the film-forming additive is difficult to be evenly dispersed on the surface of the negative electrode plate 230, and the SEI film formed by the film-forming additive on the surface of the negative electrode plate 230 is too thick, which increases the resistance of active lithium ions in the electrolyte 100 to pass through the SEI film, thereby increasing the polarization of the battery 200 and reducing the cycle performance of the battery 200.
[0073] Preferably, the value of a / b satisfies the range of 0.1≤a / b<1. Specifically, the value of a / b may be, but is not limited to, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.99, etc.
[0074] In the preferred range, the value of a / b satisfies the range of 0.1≤a / b<1. In other words, in the electrolyte 100, the mass fraction of the wetting additive is less than the mass fraction of the film-forming additive. On the one hand, the wetting additive can improve the wetting performance of the electrolyte 100; on the other hand, the wetting additive can chelate the free lithium ions in the electrolyte 100. The wetting additive is preferentially adsorbed on the surface of the negative electrode plate 230 when the battery 200 is formed. When the film-forming additive is decomposed, the film-forming additive is more likely to generate a SEI film with a higher degree of polymerization under the influence of the electron-donating effect of the ether bond of the wetting additive, and is uniformly attached to the surface of the negative electrode plate 230 with the wetting additive as a fulcrum. The SEI film formed by the wetting additive and the film-forming additive on the surface of the negative electrode plate 230 not only has a high degree of polymerization, but also has high stability, which can slow down the speed at which the electrolyte 100 is consumed during the charge and discharge cycle. In other words, the electrolyte 100 has a good low consumption capacity, so that the battery 200 has a good cycle performance. On the other hand, the wetting additive can be prevented from chelating too many lithium ions and reducing the amount of active lithium ions in the battery 200, so that the battery 200 has both high energy efficiency, good cycle stability and long cycle life.
[0075] Optionally, in some embodiments, the mass fraction b of the film-forming additive is in the range of 0.2%≤b≤8%.
[0076] Specifically, the mass fraction b of the film-forming additive can be, but is not limited to, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.7%, 3.8%, 4%, 4.2%, 4.3%, 4.5%, 4.7%, 4.9%, 5%, 5.3%, 5.5%, 5.8%, 6.2%, 6.5%, 6.8%, 7%, 7.2%, 7.5%, 7.7% and 8%, etc.
[0077] In this embodiment, when the mass fraction b of the film-forming additive satisfies the range of 0.2%≤b≤8%, the mass fraction of the film-forming additive is within a reasonable range, and the film-forming additive can be evenly distributed on the surface of the negative electrode plate 230 under the guidance of the impregnation additive, and with the impregnation additive as a fulcrum, a stable and highly polymerized SEI film is formed on the surface of the negative electrode plate 230 to slow down the speed at which the electrolyte 100 is consumed during the charge and discharge cycle. With the increase of the compaction density of the positive electrode plate 210 and the compaction density of the negative electrode plate 230, the coating mass of the positive electrode active material and the coating mass of the negative electrode plate 230 increase, the space for arranging the electrolyte 100 in the battery 200 is reduced, and the electrolyte 100 has a good low consumption performance, so that after a period of charge and discharge cycles of the battery 200, there is still more electrolyte 100 in the battery 200, so that the battery 200 has a longer service life. When the mass fraction of the film-forming additive is too large, the SEI film formed by the film-forming additive on the surface of the negative electrode plate 230 is too thick, which increases the resistance of the active lithium ions in the electrolyte 100 to pass through the SEI film, increases the polarization of the battery 200, and reduces the cycle performance of the battery 200. When the mass fraction of the film-forming additive is too small, the SEI film formed by the film-forming additive on the surface of the negative electrode plate 230 is too thin, and the SEI film is easy to rupture to form some highly active sites, which accelerates the deposition and dissolution rate of lithium ions at these sites, thereby possibly causing lithium precipitation and reducing the safety performance of the battery 200.
[0078] Optionally, in some embodiments, the film-forming additive includes at least one of vinylene carbonate, 4,5-dimethylvinylene carbonate, 4,5-divinylvinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, catechol carbonate, vinyl vinyl carbonate, trifluoropropylene carbonate, and methylene vinyl carbonate.
[0079] Among them, the structural formula of vinylene carbonate is The structural formula of 4,5-dimethyl vinylene carbonate is The structural formula of 4,5-divinyl vinylene carbonate is
[0080] In this embodiment, the film-forming additive is selected from at least one of vinylene carbonate, 4,5-dimethyl vinylene carbonate, 4,5-divinyl vinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, catechol carbonate, vinyl carbonate, trifluoropropylene carbonate, and methylene carbonate. When the film-forming additive and the wetting additive are compounded, the repeating unit ether bond of the wetting additive preferentially chelates lithium ions and adsorbs on the surface of the negative electrode plate 230. Under the influence of the electron donation effect of the ether bond, the film-forming additive is more likely to open the ring and A SEI film with a higher degree of polymerization is formed to adhere to the surface of the negative electrode plate 230, so that the interface between the negative electrode plate 230 and the electrolyte 100 has a stable SEI film with a high degree of polymerization. It is known that the higher the degree of polymerization of the SEI film, the lower its solubility in the electrolyte 100, and the less soluble it is in the electrolyte 100, so that the SEI film has a higher stability in the electrolyte 100, so as to slow down the consumption of the electrolyte 100 in the subsequent charging and discharging process, so that the electrolyte 100 has a better low consumption capability, and the battery 200 has a longer service life.
[0081] Optionally, in some embodiments, the electrolyte 100 further includes a solvent, and the solvent is used to dissolve the wetting additive. In the electrolyte 100, the mass fraction c of the solvent is in the range of 50%≤c≤90%.
[0082] It can be understood that, in the electrolyte 100 , the mass fraction c of the solvent is the ratio of the mass of the solvent to the mass of the electrolyte 100 .
[0083] Specifically, the mass fraction c of the solvent can be, but is not limited to, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 65%, 66%, 67%, 69%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 85%, 86%, 88% and 90%, etc.
[0084] In this embodiment, when the mass fraction c of the solvent satisfies the range of 50%≤c≤90%, the mass fraction of the solvent is within a reasonable range, the solvent can dissolve the wetting additive and the film-forming additive, and under the action of the wetting additive, the positive electrode plate 210 and the negative electrode plate 230 have a good wetting effect, so as to reduce the impedance of lithium ions in the electrolyte 100 transmitted in the solvent, and reduce the impedance of lithium ions from the electrolyte 100 to and from the positive electrode plate 210 and / or the negative electrode plate 230, reduce the loss of lithium ions, and make the electrolyte 100 have good cycle performance. In addition, the solvent, the wetting additive and the film-forming additive cooperate with each other to form a stable and highly polymerized SEI film on the surface of the negative electrode plate 230, further improving the cycle performance of the battery 200 when the electrolyte 100 is applied to the battery 200.
[0085] Optionally, the solvent is selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, and γ-butyrolactone.
[0086] Optionally, the electrolyte 100 further includes a lithium salt, which is dissolved in the solvent and provides active lithium ions for the battery 200 .
[0087] Optionally, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), and lithium trifluoromethanesulfonate.
[0088] Optionally, in the electrolyte 100, the concentration of the lithium salt satisfies the range of 0.6 mol / L to 1.5 mol / L. Specifically, the concentration of the lithium salt may be, but is not limited to, 0.6 mol / L, 0.65 mol / L, 0.7 mol / L, 0.75 mol / L, 0.8 mol / L, 0.85 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, etc.
[0089] Optionally, in some embodiments, the electrolyte 100 further includes a preset additive, and the preset additive includes at least one of vinyl sulfate (DTD), tris(trimethylsilyl) phosphate, tris(trimethylsilyl) borate, adiponitrile, succinonitrile, and 1,3,6-hexanetrinitrile. The preset additive can participate in SEI film formation, optimize the components of the SEI film, reduce the consumption of the electrolyte 100, and improve the cycle performance of the battery 200.
[0090] In some embodiments, the mass fraction of the preset additive satisfies the range of 0.5% to 8%. Specifically, the mass fraction of the XX additive may be, but is not limited to, 0.5%, 1%, 1.3%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.7%, 7%, 7.5%, 8%, etc.
[0091] The technical solution of this application is further introduced in the following with multiple embodiments:
[0092] Example 1 to Example 26, Comparative Example 1 to Comparative Example 6:
[0093] 1. Preparation of electrolyte 100:
[0094] In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are mixed in a mass ratio of 1:1:1, and then the dried electrolyte lithium salt lithium hexafluorophosphate is dissolved in the solvent, stirred until completely dissolved and uniformly dissolved, and fluoroethylene carbonate, a wetting additive, and a film-forming additive are added. After mixing evenly, the electrolyte 100 of Examples 1 to 26 and Comparative Examples 1 to 6 is obtained. The obtained electrolyte 100 is composed as follows: the solvent composition is ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1 (mass ratio), the lithium salt concentration is 1 mol / L, and the content of fluoroethylene carbonate is 3%.
[0095] Among them, in the electrolyte 100 of Examples 1 to 26 and Comparative Examples 1 to 6, the type of wetting additive, the mass fraction a of the wetting additive, the type of film-forming additive, the mass fraction b of the film-forming additive, and the value of a / b are as shown in Table 1.
[0096] 2. Preparation of positive electrode sheet 210:
[0097] The positive electrode active material lithium iron phosphate (LiFePO4), conductive carbon black (Super-P), and binder PVDF (polyvinylidene fluoride) are mixed in a mass ratio of 94:3:3; then N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 60wt%, and stirred evenly, and then the positive electrode slurry is evenly coated on one surface of a positive electrode current collector layer (aluminum foil) with a thickness of 10μm, and the coating weight of the positive electrode slurry is 350mg / 1540.25mm 2 Then, after drying, cold pressing, slitting and cutting, the positive electrode sheet 210 is obtained. The single-sided thickness of the positive electrode active material layer is 100 μm.
[0098] It can be understood that in the positive electrode sheet 210, the coating weight of the positive electrode active material meets the range of: 350mg / 1540.25mm2 Up to 400mg / 1540.25mm 2 , that is, the coating weight of the positive electrode slurry meets the range of 350mg / 1540.25mm 2 Up to 400mg / 1540.25mm 2 , the coating weight of the positive electrode active material is relatively high.
[0099] 3. Preparation of negative electrode sheet 230:
[0100] The negative electrode active material artificial graphite, thickener sodium carboxymethyl cellulose (CMC), conductive carbon black (Super-P) and binder styrene butadiene rubber latex (SBR) are mixed in a mass ratio of 96:2:1:1, deionized water is added, and a negative electrode slurry with a solid content of 50wt% is prepared and stirred evenly. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector layer (copper foil) with a thickness of 6μm, and after drying, cold pressing, slitting and cutting, a negative electrode sheet 230 is obtained. The single-sided thickness of the negative electrode active material layer is 70μm.
[0101] 4. Preparation of the diaphragm 220:
[0102] The separator 220 is a 16 um polyethylene film (PE).
[0103] 5. Assembly of battery 200:
[0104] The positive electrode sheet 210, separator 220, and negative electrode sheet 230 are stacked in order so that the separator 220 is located between the positive electrode sheet 210 and the negative electrode sheet 230 to play an isolating role, and then they are wound into a bare battery cell; after welding the pole ears, the bare battery 200 is placed in an outer packaging shell, and after drying, the above-mentioned electrolyte 100 is injected, and after vacuum packaging, standing, forming, shaping, etc., the implementation batteries 1 to 26 and the comparison batteries 1 to 6 are finally prepared.
[0105] Among them, the electrolyte 100 of Example 1 is applied to the implementation battery 1, the electrolyte 100 of Example 2 is applied to the implementation battery 2, the electrolyte 100 of Comparative Example 1 is applied to the comparison battery 1, the electrolyte 100 of Comparative Example 2 is applied to the comparison battery 2, and so on.
[0106] Table 1 below shows the component parameters of the electrolyte 100 in Examples 1 to 26 and Comparative Examples 1 to 6.
[0107] Table 1: Component parameters of the electrolyte 100 in Examples 1 to 26 and Comparative Examples 1 to 6.
[0108]
[0109]
[0110] Among them, in Table 1, the type of wetting additive 1-1 is Types of wetting additives 1-2 are Types of wetting additives 1-3 are Type 2-1 of film-forming additives is Types of film-forming additives 2-2 are Types of film-forming additives 2-3 are
[0111] Performance tests of implementation battery 1 to implementation battery 26 and comparison battery 1 to comparison battery 6:
[0112] Charge and discharge cycle test:
[0113] The above-mentioned implementation batteries 1 to implementation batteries 26 and comparison batteries 1 to comparison batteries 6 were subjected to constant current charge and discharge cycle tests on a charge and discharge instrument. The test temperature was 25°C, the charge and discharge rate was 1C (the size of the charge and discharge current is usually expressed by the charge and discharge rate, and the calculation formula of the charge and discharge current is: charge and discharge current = charge and discharge rate × rated capacity of battery 200), the charge and discharge voltage window was 2.5V to 3.65V (that is, the charge cut-off voltage of battery 200 is 3.65V, and the discharge cut-off voltage of battery 200 is 2.5V; it is generally believed that when the charge cut-off voltage is ≥4V, the charge cut-off voltage of battery 200 is higher), and the capacity retention rate after 3000 cycles was calculated. The calculation formula is: capacity retention rate after the Nth cycle = (discharge capacity after the Nth cycle / discharge capacity of the first cycle) × 100%.
[0114] A complete charge and discharge is usually called a charge and discharge cycle, that is, the battery 200 is first charged from 2.5V to 3.65V, and then discharged from 4.2V to 3.65V, thus forming a charge and discharge cycle. Cycle N times means repeating the above process N times.
[0115] Table 2 below shows the performance parameters of implementation batteries 1 to implementation batteries 26 and comparison batteries 1 to comparison batteries 6.
[0116] Table 2: Performance parameters of implementation batteries 1 to implementation batteries 26 and comparative batteries 1 to comparative batteries 6.
[0117]
[0118]
[0119] Please refer to Table 1 and Table 2. In the first aspect, please refer to the data of Comparative Examples 1 to 6. It can be seen from the data of Comparative Examples 1 to 3 that the electrolyte 100 in Comparative Example 1 does not include a wetting additive or a film-forming additive, and the electrolyte 100 in Comparative Examples 2 and 3 only includes a wetting additive but not a film-forming additive, and the mass fraction of the wetting additive in Comparative Example 2 is too small, and the mass fraction of the wetting additive in Comparative Example 3 is too large. The cycle capacity retention rate of Comparative Battery 2 is higher than that of Comparative Battery 1, and the cycle capacity retention rate of Comparative Battery 3 is lower than that of Comparative Battery 1. This shows that adding the wetting additive to the electrolyte 100 can improve the wetting performance of the electrolyte 100 on the positive electrode sheet 210 and / or the negative electrode sheet 230, so as to improve the cycle performance of the battery 200. However, when the mass fraction of the wetting additive is too small, the cycle performance improvement effect of the battery 200 is very small. When the mass fraction of the impregnation additive is too large, it may cause the negative effect of binding more active lithium ions, and it is also difficult to improve the cycle performance of the battery 200. From the data of Comparative Examples 1 and 4, it can be seen that the electrolyte 100 in Comparative Example 4 is added with a film-forming additive, and the capacity retention rate of Comparative Battery 4 is higher than that of Comparative Battery 1, which shows that adding a film-forming additive to the electrolyte 100 helps to form a stable SEI film on the surface of the negative electrode plate 230 to improve the cycle performance of the battery 200. From the data of Comparative Examples 2 and 5, and Comparative Examples 3 and 6, it can be seen that the impregnation additive and the film-forming additive are compounded, and the low consumption performance of the electrolyte 100 can be improved while improving the impregnation performance of the electrolyte 100, thereby further improving the cycle performance of the battery 200. However, the mass fraction of the film-forming additive in Comparative Example 5 is too large, and the mass fraction of the film-forming additive in Comparative Example 3 is too small, so that the improvement of Comparative Battery 5 and Comparative Battery 6 is not large compared with Comparative Battery 1. In other words, although too much or too little mass fraction of the film-forming additive can improve the cycle performance of the battery 200 to a certain extent, the degree of improvement is not large.
[0120] In the second aspect, it can be seen from the data of Examples 1 to 6 and Comparative Examples 1 to 3 that the electrolyte 100 of Examples 1 to 6 includes a wetting additive, and the type of the wetting additive is In the electrolyte 100 of Examples 1 to 6, the mass fraction a of the wetting additive satisfies the range of 0.05%≤a≤2%, so that the capacity retention rates of the implementation batteries 1 to 6 are higher than those of the comparison batteries 1 to 3, and in the implementation batteries 1 to 6, as the mass fraction of the wetting additive gradually increases, the capacity retention rate of the battery 200 shows a trend of first increasing and then decreasing. This is because: when the electrolyte 100 includes the wetting additive, the wetting additive can serve as a transition substance between the electrolyte 100 and the air, and the hydrophilic ether oxygen chain segment is facing the inside of the electrolyte 100, and the hydrophobic di(trimethylsilyloxy)methylsilyl group is arranged toward the air to reduce the attraction of the inside of the electrolyte 100 to the interface molecular layer on the side of the electrolyte 100 close to the air, thereby reducing the surface tension of the electrolyte 100, so that the electrolyte 100 has better cycle performance for the positive electrode plate 210 and / or the negative electrode plate 230. However, when the mass fraction of the wetting additive is small, the wetting additive does not significantly improve the wetting performance of the electrolyte 100, so that the cycle performance of the battery 200 is not significantly improved. In addition, as the mass fraction of the wetting additive in the electrolyte 100 increases, the more ether bonds there are in the wetting additive, the more lithium ions chelated and bound by the wetting additive, and the rate of migration of the lithium ions in the electrolyte 100 is reduced, thereby increasing the polarization of the battery 200, increasing the internal resistance of the battery 200, reducing the rate performance and energy efficiency of the battery 200, and also reducing the cycle stability of the battery 200. Preferably, when the mass fraction a of the wetting additive is 0.5%, the electrolyte 100 has relatively good wetting performance, and the cycle performance of the battery 4 is better.
[0121] From the data of Examples 7 to 9 and Comparative Example 1, it can be seen that the electrolyte 100 of Examples 7 to 9 includes a wetting additive, and the type of the wetting additive is In the electrolyte 100 of Examples 7 to 9, the mass fraction a of the wetting additive satisfies the range of 0.05%≤a≤2%, so that the capacity retention rates of Implementation Battery 7 to Implementation Battery 9 are higher than that of Comparative Battery 1, and in Implementation Battery 7 to Implementation Battery 9, as the mass fraction of the wetting additive gradually increases, the capacity retention rate of the battery 200 shows a trend of first increasing and then decreasing. Preferably, when the mass fraction a of the wetting additive is 0.5%, the electrolyte 100 has relatively good wetting performance, and the cycle performance of Implementation Battery 8 is better.
[0122] From the data of Examples 10 to 12 and Comparative Example 1, it can be seen that the electrolyte 100 of Examples 10 to 12 includes a wetting additive, and the type of the wetting additive is In the electrolyte 100 of Examples 10 to 12, the mass fraction a of the wetting additive satisfies the range of 0.05%≤a≤2%, so that the capacity retention rates of the implementation batteries 10 to 12 are higher than those of the comparison battery 1, and in the implementation batteries 10 to 12, as the mass fraction of the wetting additive gradually increases, the capacity retention rate of the battery 200 shows a trend of first increasing and then decreasing. Preferably, when the mass fraction a of the wetting additive is 0.5%, the electrolyte 100 has relatively better wetting performance, and the cycle performance of the implementation battery 11 is better.
[0123] In summary, from the data of Examples 1 to 12 and Comparative Examples 1 to 3, it can be seen that as the mass fraction of the wetting additive gradually increases, the capacity retention rate of the battery 200 shows a trend of first increasing and then decreasing. And when the coating weight of the positive electrode active material is high, the wetting additive is added to the electrolyte 100, and the wetting additive can still improve the wetting performance of the electrolyte 100 on the positive electrode sheet 210 and the negative electrode sheet 230. In addition, from the data of Examples 4, 8 and 11, under the same other conditions, when the structural formula of the wetting additive is: When n=8, the electrolyte 100 has better wetting performance, so that the battery 4 has better cycle performance. This is because: when n=8, the number of repeating units -OCO- of the polyether is within a reasonable range, so that the polyether in the wetting additive can fully exert its hydrophilic function, and the di(trimethylsilyl)methylsilyl group can fully exert its hydrophobic function, so that the wetting additive can effectively improve the wetting performance of the electrolyte 100, and finally improve the cycle performance of the battery 200. In Example 8, the value of n is 2, and the ether oxygen segment in the wetting additive is relatively small, so that the hydrophilic effect of the polyether structure of the wetting additive is relatively weak, which weakens the effect of the wetting additive on improving the wetting performance of the electrolyte 100, thereby causing the capacity retention rate of the battery 8 to be relatively low. In Example 11, the value of n is 18, the chain segment of the polyether is too long, and the more ether oxygen structures there are in the wetting additive, so that when the wetting additive is applied to the electrolyte 100, more ether oxygen structures will chelate more lithium ions, so that the wetting additive binds more lithium ions, thereby reducing the amount of active ions in the electrolyte 100, so that the capacity retention rate of the implemented battery 11 is low.
[0124] In the third aspect, it can be seen from the data of Examples 13 to 17 and Example 3 that the electrolyte 100 of Examples 13 to 17 includes not only a wetting additive but also a film-forming additive, and the type of the film-forming additive is In Examples 13 to 17, the mass fraction b of the film-forming additive satisfies the range of 0.2%≤b≤8%, and the value of a / b satisfies the range of 0.02≤a / b≤4, so that the capacity retention rates of Implementation Battery 13 to Implementation Battery 17 are all higher than the capacity retention rate of Implementation Battery 4, and as the mass fraction of the film-forming additive gradually increases, the capacity retention rate of the corresponding battery 200 shows a trend of first increasing and then decreasing. This is because: the wetting additive and the film-forming additive cooperate with each other, the wetting additive can chelate free lithium ions in the electrolyte 100, and the wetting additive is preferentially adsorbed on the surface of the negative electrode plate 230 when the battery 200 is formed. When the film-forming additive is decomposed in the chemical composition, the film-forming additive is under the influence of the electron donation effect of the ether bond of the wetting additive. It is easier to generate an SEI film with a higher degree of polymerization, and the film is evenly attached to the surface of the negative electrode plate 230 with the wetting additive as a fulcrum. The SEI film formed on the surface of the negative electrode plate 230 by the combination of the wetting additive and the film-forming additive not only has a high degree of polymerization, but also has a high stability, which can slow down the speed at which the electrolyte 100 is consumed in the charge and discharge cycle. In other words, the electrolyte 100 not only has good wetting performance, but also has good low consumption capacity, so that the cycle performance of the implementation battery 13 to the implementation battery 17 is better than the cycle performance of the implementation battery 4. However, when the mass fraction of the film-forming additive is too small, the SEI film formed by the film-forming additive on the surface of the negative electrode plate 230 is too thin, and the SEI film is easy to break and form some highly active sites, which accelerates the deposition and dissolution rate of lithium ions at these sites, so that lithium precipitation and other phenomena may occur, reducing the cycle performance and safety performance of the battery 200. When the mass fraction of the film-forming additive is too large, the SEI film formed by the film-forming additive on the surface of the negative electrode plate 230 is too thick, which increases the resistance of the active lithium ions in the electrolyte 100 to pass through the SEI film, increases the polarization of the battery 200, and reduces the cycle performance of the battery 200. Preferably, when the mass fraction b of the film-forming additive is 2%, the electrolyte 100 has relatively good wetting performance and low consumption capacity, and the cycle performance of the battery 15 is better.
[0125] From the data of Examples 18 to 20 and Example 3, it can be seen that the electrolyte 100 of Examples 18 to 20 includes not only a wetting additive but also a film-forming additive, and the types of the film-forming additive are In Examples 18 to 20, the mass fraction b of the film-forming additive satisfies the range of 0.2%≤b≤8%, and the value of a / b satisfies the range of 0.02≤a / b≤4, so that the capacity retention rates of Implementation Battery 18 to Implementation Battery 20 are all higher than the capacity retention rate of Implementation Battery 4, and as the mass fraction of the film-forming additive gradually increases, the capacity retention rate of the corresponding battery 200 shows a trend of first increasing and then decreasing. Preferably, when the mass fraction b of the film-forming additive is 2%, the electrolyte 100 has relatively superior wetting performance and low consumption capacity, and the cycle performance of Implementation Battery 19 is better.
[0126] From the data of Examples 21 to 23 and Example 4, it can be seen that the electrolyte 100 of Examples 21 to 23 includes not only a wetting additive but also a film-forming additive, and the types of the film-forming additive are In Examples 21 to 23, the mass fraction b of the film-forming additive satisfies the range of 0.2%≤b≤8%, and the value of a / b satisfies the range of 0.02≤a / b≤4, so that the capacity retention rates of Implementation Battery 21 to Implementation Battery 23 are all higher than the capacity retention rate of Implementation Battery 4, and as the mass fraction of the film-forming additive gradually increases, the capacity retention rate of the corresponding battery 200 shows a trend of first increasing and then decreasing. Preferably, when the mass fraction b of the film-forming additive is 2%, the electrolyte 100 has relatively superior wetting performance and low consumption capacity, and the cycle performance of Implementation Battery 22 is better.
[0127] In summary, from the data of Examples 13 to 23 and Example 4, it can be seen that, under the same conditions, as the mass fraction of the film-forming additive gradually increases, the corresponding capacity retention rate of the battery 200 shows a trend of first increasing and then decreasing. In addition, from the data of Examples 15, 19 and 22, it can be seen that, under the same conditions, the capacity retention rate of the battery 15 is better than that of the battery 19 and the battery 22, which shows that when the type of the film-forming additive is When the wetting additive cooperates with the film-forming additive, the degree of polymerization of the SEI film formed on the surface of the negative electrode plate 230 is within a reasonable range, so that in the subsequent charge and discharge cycles, the SEI film is more stable and not easy to be damaged, and the repair of the SEI film by the electrolyte 100 is reduced, thereby slowing down the consumption of the electrolyte 100. In other words, the electrolyte 100 has a good low consumption performance, so that the battery 200 has a good cycle performance. When the type of the film-forming additive is When the wetting additive and the film-forming additive cooperate with each other, the polymerization degree of the SEI film formed on the surface of the negative electrode plate 230 is relatively small, so that the SEI film is insufficient to protect the interface between the negative electrode plate 230 and the electrolyte 100, and the capacity retention rate of the battery 19 is low. When the type of the film-forming additive is When the wetting additive cooperates with the film-forming additive, the degree of polymerization of the SEI film formed on the surface of the negative electrode plate 230 is relatively large, which increases the impedance of lithium ions passing through the SEI film, thereby causing the capacity retention rate of the implemented battery 22 to be relatively low.
[0128] In the fourth aspect, it can be seen from the data of Example 15, Example 24 to Example 26, Comparative Example 5 and Comparative Example 6 that the electrolyte 100 of Example 15, Example 24 to Example 26 includes both a wetting additive and a film-forming additive, and the mass fraction a of the wetting additive and the mass fraction b of the film-forming additive satisfy the range: 0.02≤a / b≤4, the value of a / b in Comparative Example 5 is too small, and the value of a / b in Comparative Example 6 is too large, so that the capacity retention rate of the implementation battery 15, the implementation battery 24 to the implementation battery 26 is better than the capacity retention rate of the comparative battery 5, and the implementation battery 15, the implementation battery 24 to the implementation battery 26 is better than the capacity retention rate of the comparative battery 5, and the implementation battery 15, the implementation battery 24 to the implementation battery 26 is better than the capacity retention rate of the comparative battery 5. The capacity retention rate of the battery 26 is better than that of the comparative battery 6 because: when the value of a / b meets a reasonable range, the wetting additive and the film-forming additive have a good synergistic effect. On the one hand, the wetting additive can be enriched in the contact interface between the electrolyte 100 and the positive electrode sheet 210 and the negative electrode sheet 230. The wetting additive serves as a transition substance between the electrolyte 100 and the positive electrode sheet 210 and the negative electrode sheet 230 to improve the wetting performance of the electrolyte 100 on the positive electrode sheet 210 and the negative electrode sheet 230, and improve the cycle performance of the battery 200. On the other hand, the wetting additive and the film-forming additive cooperate with each other so that the film-forming additive is evenly dispersed on the surface of the negative electrode sheet 230, and a uniform, stable and highly polymerized SEI film is formed on the surface of the negative electrode sheet 230 to slow down the consumption rate of the electrolyte 100 during the charge and discharge cycle of the battery 200. In summary, the wetting additive improves the wetting performance of the electrolyte 100, and the wetting additive and the film-forming additive cooperate with each other to improve the low consumption performance of the electrolyte 100, thereby improving the cycle performance of the battery 200 when the electrolyte 100 is applied to the battery 200. Preferably, when the value of a / b is 1 / 4, the wetting additive and the film-forming additive have the best synergistic effect, so that the battery 15 has the best capacity retention rate. When the value of a / b is too small, the wetting additive has no obvious effect on improving the wetting performance of the electrolyte 100, which reduces the cycle performance of the corresponding battery 200. When the value of a / b is too large, there are too many ether bonds in the wetting additive, so that the lithium ions chelated and bound by the wetting additive are too many, which reduces the migration rate of the lithium ions in the electrolyte 100, thereby increasing the polarization of the battery 200, so that the internal resistance of the battery 200 increases, the rate performance and energy efficiency of the battery 200 are reduced, and the cycle stability of the battery 200 is also reduced. In addition, the SEI film formed by the film-forming additive on the surface of the negative electrode plate 230 is too thin, and the SEI film is easily broken to form some highly active sites, which accelerates the deposition and dissolution rate of lithium ions at these sites, thereby causing lithium precipitation and other phenomena, and may also reduce the cycle performance and safety performance of the battery 200.
[0129] See also Figure 2 and Figure 3 The present application also provides an electrical device 300 , which includes: a device body 310 and a battery 200 provided in the present application, and the battery 200 supplies power to the device body 310 .
[0130] It can be understood that the battery 200 is electrically connected to the device body 310 .
[0131] In this embodiment, the electrolyte 100 of the battery 200 has good wetting performance on the positive electrode plate 210 and the negative electrode plate 230, so that the battery 200 has good cycle performance and a long cycle life. When the battery 200 is applied to the power-consuming device 300, the battery 200 can provide stable power to the device body 310, which is conducive to improving the user experience.
[0132] Optionally, the power-consuming device 300 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Figure 2 The electrical equipment 300 of the embodiment is an energy storage battery cabinet.
[0133] It can be understood that the electric device 300 described in this embodiment is merely a form of the electric device 300 used by the battery 200, and should not be understood as a limitation on the electric device 300 provided in this application, nor should it be understood as a limitation on the electric device 300 provided in each embodiment of this application.
[0134] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.
[0135] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. An electrolyte, characterized in that: The electrolyte includes a wetting additive, the wetting additive is a polyether, and the end group of the wetting additive includes a di(trimethylsilyloxy)methylsilyl group.
2. The electrolyte according to claim 1, characterized in that The structural formula of the wetting additive is: The range of n is: 2≤n≤20.
3. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass fraction a of the wetting additive is in the range of 0.05%≤a≤2%.
4. The electrolyte according to claim 3, characterized in that The electrolyte further includes a film-forming additive, which is a cyclic carbonate additive. In the electrolyte, the mass fraction of the film-forming additive is b, and the electrolyte satisfies the relationship: 0.02≤a / b≤4.
5. The electrolyte according to claim 4, characterized in that The mass fraction b of the film-forming additive is in the range of 0.2%≤b≤8%.
6. The electrolyte according to claim 4, characterized in that The film-forming additive includes at least one of vinylene carbonate, 4,5-dimethylvinylene carbonate, 4,5-divinylvinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, catechol carbonate, vinylethylene carbonate, trifluoropropylene carbonate, and methyleneethylene carbonate.
7. The electrolyte according to claim 1, characterized in that The wetting additive is selected from and One or more of .
8. The electrolyte according to any one of claims 1 to 7, characterized in that The electrolyte further includes a solvent, and the solvent is used to dissolve the wetting additive. In the electrolyte, the mass fraction c of the solvent is in the range of 50%≤c≤90%.
9. A battery, characterized in that: The battery comprises: Positive electrode; Diaphragm; A negative electrode; and The electrolyte according to any one of claims 1 to 8, wherein the electrolyte is used to wet at least a portion of the positive electrode sheet, the separator and the negative electrode sheet.
10. An electrical device, characterized in that: The electrical equipment includes: The device itself; and The battery of claim 9, wherein the battery is used to power the device body.